Estudo dos processos de extração do óleo de candeia (Eremanthus erythropappus) com fluidos pressurizados e solvente assistido por ultrassom - Santos, Kátia Andressa (2018)
Candeia (Eremanthus erythropappus) is a native species of the Brazilian Atlantic forest from which an essential oil with high concentration of sesquiterpene α-bisabolol is extracted. α-Bisabolol is an active principle of important application in the cosmetic and pharmaceutical industries due to its anti-inflammatory, antispasmodic, sedative, antiallergic, anti-irritant, cicatrizant and vermifugal properties. Steam distillation is the most common method used to obtain this oil, with requires long periods of time extraction besides the degradation of thermosensitive compounds. Within this context, the aim of this study was to evaluate the quality of the candeia wood oils obtained by non-conventional methods of extraction (supercritical technology by using carbon dioxide and cosolvents, pressurized liquid and ultrasound-assisted extraction), in terms of oil yield, bisabolol content and antioxidant activity. In addition, the oil re-extraction from the industrial residue was also evaluated. The extractions were carried out with CO2 at temperatures of 40, 55 and 70 oC and pressures of 160, 200 and 240 bar, with a solvent mass flow rate of 1.96 x 10−3 kg min−1 and 120 min of total extraction. The highest extraction yield obtained was 1.42 wt% for the candeia wood and 0.41 wt% for the residue, both at 70 oC and 240 bar, and this condition was selected to perform the extractions using cosolvents. Ethanol and ethyl acetate were added to supercritical CO2 at concentrations of 1, 3 and 5 % (v/v), obtaining up to 2.35 wt% of yield. The Soxhlet (360 min) and pressurized liquid (40, 55 and 70 oC; 100 bar and 20 min) extractions showed the affinity of the candeia compounds for polar solvents and the positive effect of the temperature on the yield, which varied from 0.53 to 7.23 wt%. A Box-Benhken design was employed to evaluate the effect of the variables temperature (40, 50 and 60 oC), n-hexane volume to wood mass (10, 15 and 20 mL g-1) and nominal power (150, 300 and 450 W) on the yield of ultrasound-assisted extractions, obtaining in 7 minutes of extraction, up to 83% of the yield obtained in the conventional technique in Soxhlet (1.57 wt%), with a solvent volume 2.5 times smaller. The major compounds identified in the candeia oil were the sesquiterpenes α-bisabolol, eremanthin and costunolide, and the α-bisabolol content in the oil is favored by the lowest CO2 density, with 74.45 % being obtained for the candeia wood and 50.62 % for the residue, in both cases in oil extracted at 70 oC and 160 bar. The addition of ethanol and ethyl acetate cosolvents to CO2 increased the α-bisabolol yield by 41 %. Also, the cosolvents increased the amount of total phenolic content in the oil, and consequently, its antioxidant capacity. The oil fractionation by column chromatography was efficient for α-bisabolol isolation. However, unlike the candeia wood oil, this compound was not effective in inhibiting the Staphylococcus aureus growth. In relation to the supercritical extractions, the Sovová mathematical model presented a good adjustment to the experimental data for all the conditions used.